Shelter management practices followed by the Pantja goat herds in Tarai region of Uttarakhand (Indian Journal of Animal Production and Management, 2018)
A bench mark survey was conducted to collect the base line information from the goat rearers regarding  various housing management practices with special reference to Pantja goats of Udham Singh Nagar and  Nainital districts of Tarai region of the Uttarakhand during a period of two years (April, 2015 to March, 2017).  The results of present study revealed that maximum goat rearers (59.69%) maintained the flock within  a shed near to own residences (79.84%). Majority of goat rearers (62.79%) had kachcha floor and used  temporary type of roof (84.65%). 64.50 % goat rearers had a practice to house all categories of goats in  one shed and 69.77% goat keepers housed the goats at night. 78.29 % goat rearers did not have feeder  in the goat shed and 69.46% goat rearers had no drainage system in the shed. The effect of districts on  type of house, type of flooring, feeder in goat shed, drainage system and sanitation condition of shed were  found significant while its effect on rest of the housing practices was non-significant. It can be concluded  from the study that the scientific housing practices are generally not followed by most of the goat keepers.  Creation of awareness regarding scientific housing practices will help in improving the productivity of goats  and income of the goat keepers.
Keywords: Drainage; Flooring; Goat keepers; Housing management; Sanitation